Program Assessment – Implementing a Cycle of Continuous Improvement - Terri Gaeddert (Academic Chairpersons Conference Proceedings, 2023)
Presenter and participants will discuss challenges of assessment processes and best practices available to assessment coordinators, department chairs, and administrators to support a culture of assessment for continuous improvement. The presenter will share how adjusting the timeline of assessment reporting provided for increased data collection and more meaningful discussion and reflection on data trends.
Keywords: assessment; evaluation; continuous improvement; student learning outcomes; processes